TRI HITA KARANA BASED PARENTING AS THE MAIN PILLAR OF STUDENT CHARACTER EDUCATION AMID COVID 19 PANDEMIC - susiani, ketut; Kadek Suranata (UHN I Gusti Bagus Sugriwa Denpasar, 2022)
Character education is important to be applied to students because the character of the young generation describes the character of a nation. Increasing character education amid the current Covid-19 pandemic can be done by parenting, or by involving the role of parents in raising children. Parenting plays an important role in stimulating character education because parents are the first environment they get and parents are often role models for children. Developing character by parenting can be done based on Tri Hita Karana which is the basic concept for building a community character in Bali. This article aimed to find out the benefits of parenting to insert character education for students amid pandemic. This study was qualitative research and the data were collected from the structured interviews. The research object was 20 students in elementary schools as well as their parents. The findings showed that the parenting method of character education was well implemented by parents to create the child's character as expected.